QUALITY OF IMPLEMENTING LICENSING SERVICES IN CIMAHI CITY PUBLIC SERVICE MALLS IN 2022-2023 - Ismiazi , Ramdany; Nandang Alamsah Deliarnoor; Rahman , Mulyawan (DIA: Jurnal Administrasi Publik, 2025)
This research discusses the quality of licensing services in Cimahi City Public Service Malls in 2022-2023. Public Service Malls are the government's efforts to improve the quality of integrated services. However, public services at the Cimahi City Public Service Mall are not yet fully running well with the desired goals because there are still many complaints from the public and the government. This research aims to determine the quality of public services at MPP Cimahi City. This research uses a qualitative descriptive method. The data collection techniques in this research are observation and interviews, while the data analysis techniques involve data reduction, presentation, and conclusion. The results of research in the field show that the quality of licensing services at the Cimahi City Public Service Mall in 2022-2023 is still not optimal, this is because several measures of the quality of good public services have not yet been met.